ROOSEVELT'S MAN IN EUROPE. (4th February 2016) - Weisbrode, Kenneth
Abstract : Lewis Einstein (1877–1967) was a little-known diplomat who became one of Theodore Roosevelt's closest advisers on European affairs. Roosevelt's attraction to Einstein derived not only from a keen writing style and considerable fluency in European history, literature and politics, but also from his instinct for anticipating the future of European rivalries and for the important role the United States could play there in preserving peace. The two men shared a perspective on the twentieth century that saw the United States as a central arbiter and enforcer of international order—a position the majority of Americans would accept and promote only after the Second World War. The relationship between Roosevelt and Einstein sheds light on the rising status of American diplomacy and diplomats and their self-image vis-à-vis Europe at the turn of the twentieth century.